Analisis rasio likuiditas untuk analisis laporan keuangan PT Blue Bird Tbk - Noer Adhityanthi; Alifah Salsa Bilah; Krisolita Eliani; Khusnul Khotimah Mansur (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
Undertaked a financial analysis on a company is to determine how well the company is in processing or controlling aspects in its financial statements. The purpose of this research is to review the performance, especially in the financial sector of PT Blue Bird Tbk. This study uses qualitative as well as quantitative methods which in analyzing the financial statements of PT Blue Bird Tbk used financial ratio analysis, namely the liquidity ratio. The results of this study indicate that PT Blue Bird Tbk has managed and controlled its finances well, which is indicated by the value of the liquidity ratio analysis carried out which has shown above the recommended value.